GPT Perdetry Test: Generating new meanings for new words - Malkin, Nikolay; Lanka, Sameera; Goel, Pranav; Rao, Sudha; Jojic, Nebojsa (North American Chapter of the Association for Computational Linguistics: Human Language Technologies, 2021)
Human innovation in language, such as inventing new words, is a challenge for pretrained language models. We assess the ability of one large model, GPT-3, to process new words and decide on their meaning. We create a set of nonce words and prompt GPT-3 to generate their dictionary definitions. We find GPT-3 produces plausible definitions that align with human judgments. Moreover, GPT-3’s definitions are sometimes preferred to those invented by humans, signaling its intriguing ability not just to adapt, but to add to the evolving vocabulary of the English language.